Simulation Study Of Flow Profile Of Air Chamber At Various Heat Supplied - Rani, Muhammad Rabbani Abd (Universiti Sains Malaysia, 2017)
The wind tunnel is one of the most common experimental testing facilities used in mechanical or aerospace engineering for the testing of fluid flow behaviour. The flow profile of a fluid is vital component to gets a general comprehension of how the flow profundity changes in a chamber. The viscosity and velocity of a fluid can altogether influence the route in which it flows through a chamber. The utilization of hot air is vital in these days’ application, for example, drying processes, washing processes, pasteurisation processes and so forth. Different temperature levels are connected in mechanical applications. Thus, the objective of this project is to do the flow profile of air chamber at different intake velocity so that we can determine and get overall understanding of how the flow varies in a chamber affected by the heater and stopper equipped. Next, simulation using ANSYS Workbench-Fluent software has been developed to obtain the volume rendering of the air chamber and the velocity contour at the outlet of the air chamber. From the result, it is found that the heater will affects the velocity magnitude at the outlet of the air chamber. The stopper also will affect the velocity distributed across the outlet of the air chamber.